Effects of the interrelationship of porcine somatotropin administration and dietary phosphorus on bone properties in developing gilts - Weeden, T.L.; Hansen, J.A.; Friesen, K.G.; Richert, B.T.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-two gilts (initial weight = 127 lb) were used to determine effects of the interrelationship of porcine somatotropin (pST) administration and dietary phosphorus (P) on bone mechanical properties and mineralization in finishing gilts (127 to 235 lb) and for a 35-d postfinishing phase following withdrawal of pST administration. Gilts were injected daily with placebo (control) or 4 mg pST and fed .4, .6, or .8% P in the finishing phase. When each block weight averaged 235 lb, half of the gilts were slaughtered and the first rib, femur, and third and fourth metacarpals were collected. Stress; modulus of elasticity; and ash content of rib, femur, and metacarpals were reduced and femur wall thickness was increased in pST-treated gilts. Increasing dietary P increased bending moment, stress, and ash content for all bones collected, with the exception of metacarpal stress, which was not affected. The remaining 36 gilts were individually fed 4 IbId of a common diet to assure P intake of 22.8 gld for the 35 d postfmishing phase. Gilts receiving higher levels of dietary P during the finishing phase had increased bending moment and ash content for the rib and femur; rib stress and femur wall thickness were also increased following the postfinishing phase. Gilts administered pST during the finishing phase exhibited a compensatory increase in mineralization as evidenced by equal stress values for rib, femur, and metacarpals compared to control gilts by the end of the postfinishing phase. Although bone strength and mineralization were lower in pST-treated gilts than controls at the end of the finishing phase, if pST-treated gilts were fed at least a .6% P diet (16.5 gld P) during the finishing phase, then bone strength and mineralization similar to those of control gilts could be attained with a diet containing at least 18 g P and 22.5 g Ca daily during the postfinishing phase.
Keywords: Swine; Somatotropin; Phosphorus; Gilts; Bone